UNRAVELING THE DRIVERS OF CUSTOMER LOYALTY IN SHOPEE INDONESIA: A META-ANALYSIS OF BRAND IMAGE, BRAND TRUST, E-SERVICE QUALITY, AND CUSTOMER SATISFACTION - Cahyono Arjo, Julian Grazius; Lasiyono, Utung; Afkar, Taudlikhul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to identify the factors influencing Shopee customer loyalty in Indonesia, focusing on brand image, brand trust, e-service, and customer satisfaction. The meta-analysis method is used to analyze the results of several relevant studies in this context. The meta-analysis results show that brand image has a significant positive relationship with customer loyalty, but is not significantly influenced by customer satisfaction. conversely, brand trust and e-service have a significant positive relationship with customer loyalty, and customer satisfaction partially mediates the relationship between these two factors and Shopee customer loyalty. These findings indicate that brand image has a strong direct influence on customer loyalty, while brand trust and e-service can enhance customer loyalty both directly and through customer satisfaction. This underscores the importance of building a strong brand image, high consumer trust, and good electronic services to increase customer loyalty on e-commerce platforms such as Shopee in Indonesia.